2016
DOI: 10.1038/nature16986
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of global terrestrial ecosystems to climate variability

Abstract: Here we present a novel, empirical approach to assess the relative sensitivity of ecosystems to climate variability, one property of resilience that builds on theoretical modelling work recognizing that systems closer to critical thresholds respond more sensitively to external perturbations 2 . We develop a new metric, the vegetation sensitivity index (VSI) which identifies areas sensitive to climate variability over the past 14 years. The metric uses time series data of MODIS-derived enhanced vegetation index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
690
2
12

Year Published

2017
2017
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 978 publications
(844 citation statements)
references
References 30 publications
47
690
2
12
Order By: Relevance
“…With increasing climate variability and more frequent occurrences of extreme events expected in the future 7 , research has targeted the sensitivity of ecosystems 8,9 . At the same time, recent studies have shown globally increasing leaf area index (LAI; a proxy for green vegetation cover) 10 , and aboveground biomass carbon (ABC) 11 , also known as the greening Earth 10,12 .…”
mentioning
confidence: 99%
“…With increasing climate variability and more frequent occurrences of extreme events expected in the future 7 , research has targeted the sensitivity of ecosystems 8,9 . At the same time, recent studies have shown globally increasing leaf area index (LAI; a proxy for green vegetation cover) 10 , and aboveground biomass carbon (ABC) 11 , also known as the greening Earth 10,12 .…”
mentioning
confidence: 99%
“…The estimated mean of the matrix of cells, and its respective CI, was then used to calculate the normalised confidence interval amplitude for the mean (NCIAM), which is used as a measure of the associated uncertainty (see, for example, Seddon et al [44]). The confidence interval amplitude was normalised using the corresponding mean value,…”
Section: Methodsmentioning
confidence: 99%
“…Reduced terrestrial evapotranspiration may cause a reduction in atmospheric relative humidity, although the increased lake evaporation may make up for this. CA is a hotspot of climate change [23,86], but the influence of its vast domain on local climate variability and climate change remains poorly studied due to limited regional research capacity and data sharing issues.…”
Section: Effects Of the Global Circulation Climate Change And Local mentioning
confidence: 99%